Manajemen Sulit Jalan Napas pada Pasien Pediatrik dengan Sindrom Bosman-Arhinia Mikroftalmia - Mahmud; Widodo, Untung; Loru, Martha Yuanita (Jurnal Komplikasi Anestesi, 2021)
A 12-months-old boy with Bosman-Arhinia Microphthalmia Syndrome (BAMS) will undergo surgery to replace a nasopharyngeal duct catheter after nasal reconstruction. Patients with ASA physical status 2 with BAMS and prediction of difficult airway. Patient with a history of 2 months ago went on tracheostomy surgery, facilitated by general anesthesia using the Supraglotic Airway Device (SAD) or Laringeal Mask Airway (LMA). After 3 weeks, the tracheostomy cannula was removed and the tracheostomy wound was closed. We used crash induction but found difficulty in ventilation with a facemask or with the LMA so that management was immediately carried out according to the difficult airway algorithm and intubation was successful